Praksisnær undervisning i legemiddelregning i arbeidet med å redusere testangst og styrke selvoppfattelse hos sykepleierstudenter - Røykenes, Kari; Smith, Kari; Larsen, Torill M. B. (Nordisk Tidsskrift for Helseforskning, 2015)
Alternative teaching method in dosage calculation to reduce nursing students’ test anxiety and enhance self-conceptNorwegian nursing students must pass a drug calculation test with a flawless performance if they are to qualify as nurses. This requirement is found to increase students’ test anxiety and mathematical low self-conceptual students are highly effected. The aim of the current study is to examine if participating in a special education program benefits students with high test anxiety and low self-concept in the domain of mathematics. The participants were highly involved in both planning and conducting the alternative program which had a practical approach towards both mathematics and drug calculation. We use a mixed methods approach to examine nursing students’ experiences participating in the program, and data are collected by using survey questionnaires, participants’ evaluation and a focus group interview. Ten freshman nursing students participating in the program responded to a questionnaire pre and post intervention, including a written evaluation during the program. Finally a focus group interview was conducted two years after the intervention. The survey data show a significant change in mathematics-self-concept, however, no significant reduction in test anxiety was found, but the qualitative data from the interview suggest a reduction in anxiety and higher mathematical self-concept after participating in the program.